Comparative Study the Role of artificial intelligence and their Impact on Teaching and E-learning Platforms (Duolingo, ALEKS, Coursera, QuestionPro) - E .Zargoun (African Journal of Advanced Pure and Applied Sciences, 2024)
Artificial Intelligence (AI) has rapidly transformed various sectors, and education is no exception. This paper conducts a comparative study of four leading AI-driven E-learning platforms: Duolingo, ALEKS, Coursera, and QuestionPro. By analyzing their features, methodologies, and impacts on teaching and learning, this study aims to provide insights into the effectiveness of AI in education. Duolingo employs adaptive learning algorithms to teach languages, ALEKS provides personalized learning pathways for mathematics, Coursera offers AI-enhanced course recommendations and grading systems, and QuestionPro utilizes AI for survey analytics. Through a comparative analysis, this paper evaluates the efficacy, user engagement, and learning outcomes of these platforms. The findings contribute to understanding the role of AI in shaping modern education and highlight implications for future research and development.